John's use of Ezekiel : understanding the unique perspective of the Fourth Gospel - Peterson, Brian Neil, 1966- (Minneapolis: : Fortress Press, 2015)
Scholars have long puzzled over the distinctive themes and sequence of John's narrative in contrast to the accounts in the Synoptic Gospels. Brian Neil Peterson now offers a remarkable explanation for some of the most unusual features of the Fourth Gospel, including the exalted language of the Johannine prologue; the focus upon Jesus as Word; the imagery of light and darkness, of glory and "tabernacling"; the role -- and rejection -- of prophecy; the early placement of Jesus' "cleansing" of the temple and his relation to it; the emphasis on "signs" confirming Jesus' identity; and the prominence of Jesus' "I Am" sayings. Peterson finds important connections with motifs, themes, and even the macrostructure of the book of Ezekiel at just the points of John's divergence from the synoptic narrative. His examination of events and sequence in the Fourth Gospel produces a novel understanding of John as steeped in the theology of Ezekiel -- and of the Johannine Christ as the fulfillment of the vision of Ezekiel.
The uniqueness of John's gospel -- John 1 and Ezekiel 1-3 juxtaposed -- John's use of signs and Ezekiel's sign acts -- John's placement of the cleansing of the temple in light of Ezekiel 8-11 -- John's "I am" sayings in light of Ezekiel -- John 17, 20, and Ezekiel 37 : unity, resurrection, and the insufflation -- Jesus' rebuilt "temple" and Ezekiel 40-43 -- Conclusions and implications.
Includes bibliographical references and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Influence; Bible. -- Relation to Ezekiel; Bible. -- Relation to John